Cestode Parasites of Free-Range Chickens (Gallus gallus domesticus) in the North-Eastern of Algeria - Ilyes , Medjouel; Ahmed, Benakhla (International Journal of Poultry Science, 2013)
A study was carried out on 144 local chickens (Gallus gallus domesticus), from rural area of El-Tarf to determine the prevalence of cestode parasites in the intestinal tract of the chickens. The overall prevalence rate was 88.19%, in the El-Tarf poultry. At least one species of cestodes was found on every chicken examined. Seven species of cestodes were identified in all; they had the following prevalences: Raillietina echinobothrida (83.33%), Raillietina tetragona (68.75%), Raillietina cesticillus (29.16%), Hymenolepis carioca (12.5%), Choanotaenia infundibulum (11.8%), Davainea proglottina (11.11%) and Amoebotaenia cuneata (4.16%). This study showed that there was no significant difference (p>0.05) between the prevalence of cestodes in relation to age and sex.